Dengue-1 envelope protein domain III along with PELC and CpG oligodeoxynucleotides synergistically enhances immune responses. - Chen-Yi Chiang; Ming-Hsi Huang; Chun-Hsiang Hsieh; Mei-Yu Chen; Hsueh-Hung Liu; Jy-Ping Tsai; Yi-Shiuan Li; Ching-Yun Chang; Shih-Jen Liu; Pele Chong; Chih-Hsiang Leng; Hsin-Wei Chen (PLoS Neglected Tropical Diseases, 2012)
The major weaknesses of subunit vaccines are their low immunogenicity and poor efficacy. Adjuvants can help to overcome some of these inherent defects with subunit vaccines. Here, we evaluated the efficacy of the newly developed water-in-oil-in-water multiphase emulsion system, termed PELC, in potentiating the protective capacity of dengue-1 envelope protein domain III. Unlike aluminum phosphate, dengue-1 envelope protein domain III formulated with PELC plus CpG oligodeoxynucleotides induced neutralizing antibodies against dengue-1 virus and increased the splenocyte secretion of IFN-γ after in vitro re-stimulation. The induced antibodies contained both the IgG1 and IgG2a subclasses. A rapid anamnestic neutralizing antibody response against a live dengue virus challenge was elicited at week 26 after the first immunization. These results demonstrate that PELC plus CpG oligodeoxynucleotides broaden the dengue-1 envelope protein domain III-specific immune responses. PELC plus CpG oligodeoxynucleotides is a promising adjuvant for recombinant protein based vaccination against dengue virus.